NURSING EDUCATION RESILIENCE: THE EFFECTIVE STRATEGIES TO ADDRESS THE CHALLENGES OF STAKEHOLDERS DURING THE COVID-19 PANDEMIC - Janes Jainurakhma; Inu Martina; Sekarini Sekarini; Qori Fanani; Indah Nur'aini (Universitas Negeri Malang, 2022)
Abstract: The complexity of the challenges for nursing education makes the nursing study program think hard to produce various innovations in curriculum implementation during the COVID-19 pandemic. This study aims to explore the strategy of the nursing undergraduate study program in implementing a nursing curriculum that is oriented to stakeholder demands during the COVID-19 pandemic. This study uses a qualitative approach, using interpretive phenomenological methods. Purposive and snowball sampling was used in this study to help the researchers identify the key informant, with the criteria: ten nursing lecturers who are active in giving lectures in the COVID-19 pandemic, twenty stakeholders (among them: students, nursing clinical instructors, clinical professional nurses, users of nursing graduates) and willing to be an informant. Using semi-structured interview techniques, the data obtained is then analyzed using the interactive analysis model of Miles, Huberman & Saldana. The results found five themes, including (1) Increase collaboration with instructors from the clinic; (2) Strengthening the skills of teachers with the blended learning method; (3) Streamline the learning management system; (4) Develop community-based nursing learning during pandemic; (5) Open-effective communication with stakeholders. The effectiveness of the curriculum implementation strategy during the COVID-19 pandemic requires pro-activity from the entire academic community of the nursing study program, to produce quality nursing graduates and meet the high demands of stakeholders during the multi-crisis of the COVID-19 pandemic. The success of the nursing education curriculum system during the COVID-19 pandemic is strongly influenced by the active and positive contributions and collaborations of nursing stakeholders. Keywords: COVID-19 pandemic; curriculum strategies; nursing education; resilience; stakeholders challenges.